1997
DOI: 10.1002/anie.199708761
|View full text |Cite
|
Sign up to set email alerts
|

An FT–Raman Study of the Template –Framework Interaction in AlPO4‐Based Molecular Sieves

Abstract: The organic template within molecular sieves may readily be studied by FT–Raman spectroscopy with virtually no interference from bands due to framework vibrations. FT‐Raman spectra show that morpholine and cyclohexylamine are in the protonated form within AlPO4‐based materials with the chabazite structure, while splittings of certain bands indicate specific interactions between the organic template and the framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…2) The heteroatoms influence the conformer distributions observed in the CHA materials. Differences in the position and conformation of the OSDA in aluminophosphate CHA synthesized with Mg, Mn, Si or Zn have been previously reported, and were attributed to varying template‐framework interactions due to the different heteroatoms . The present results are consistent with previous observations that the differences in occluded conformer ratios within the CHA framework are likely the result of varying template‐framework interactions caused by differences in acid site strength as well as different d‐electron counts between the metals substituted into the CHA framework .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2) The heteroatoms influence the conformer distributions observed in the CHA materials. Differences in the position and conformation of the OSDA in aluminophosphate CHA synthesized with Mg, Mn, Si or Zn have been previously reported, and were attributed to varying template‐framework interactions due to the different heteroatoms . The present results are consistent with previous observations that the differences in occluded conformer ratios within the CHA framework are likely the result of varying template‐framework interactions caused by differences in acid site strength as well as different d‐electron counts between the metals substituted into the CHA framework .…”
Section: Figurementioning
confidence: 99%
“…Differences in the position and conformation of the OSDA in aluminophosphate CHA synthesized with Mg, Mn, Si or Zn have been previously reported, and were attributed to varying template‐framework interactions due to the different heteroatoms . The present results are consistent with previous observations that the differences in occluded conformer ratios within the CHA framework are likely the result of varying template‐framework interactions caused by differences in acid site strength as well as different d‐electron counts between the metals substituted into the CHA framework . This study reinforces the proposal that the charged framework plays a role in determining the conformer ratio, with a demonstrated dependency on the acid site strength and d‐electron count, showing the importance of electrostatic and coordination chemistry interactions .…”
Section: Figurementioning
confidence: 99%
“…Aluminum phosphate, AlPO 4 , is a compound with solid bi-functional acid–bases, and has been known as an important candidate for catalyst supports or molecular sieves because of its zeolite-like structure and special properties [116]. For example, AlPO 4 has been used to catalyze the oxidation reaction of alkanes, cycloalkanes and phenols by loading transition metals in its network.…”
Section: Introductionmentioning
confidence: 99%
“…Energy difference between these two chair conformers is very low (around 1 kcal/mol in gas-phase as calculated at MP2/aug-cc-pvdz level), the equatorial one being more stable due to less steric interaction. In the Raman and IR spectra of pure liquid morpholine, contribution from both of these conformations can be detected. ,, Vedal et al reported the IR spectra of morpholine in gaseous, liquid and crystalline phases as well as Raman spectra in liquid and crystalline phases . They have assigned the peaks in these spectra to the vibrational peaks of the axial and equatorial chair conformers.…”
Section: Resultsmentioning
confidence: 99%
“…In the Raman and IR spectra of pure liquid morpholine, contribution from both of these conformations can be detected. 6,10,11 Vedal et al reported the IR spectra of morpholine in gaseous, liquid and crystalline phases as well as Raman spectra in liquid and crystalline phases. 11 They have assigned the peaks in these spectra to the vibrational peaks of the axial and equatorial chair conformers.…”
Section: Resultsmentioning
confidence: 99%